APLIKASI MOBILE GAME EDUKASI MATEMATIKA BERBASIS ANDROID APPLICATION OF EDUCATION MOBILE GAMES FOR MATH BASED ON ANDROID - Aprilianti, Yunis; Lestari, Uning; Iswahyudi, Catur (Jurnal Script, 2013)
ABSTRACTÂ The development of mobile device technology today is very fast , mobile devices can be used not only as a media of communication but also as a media of entertainment . One of popularfeaturesÂ on mobile devices is a game . In this case the game is not only used to entertain but also used as a media that gives lessons .This game is developed for a mathematical that contains material from VI grade of Elementary School . The game has 3 levels that can be selected by the players and also the material that can be accessed by the player before starting the game . The design of this game uses the accelerometer in the android operating system integratedwith Box2D Physics Engine Library . In addition , this game was built using the Framework of Libgdxand using Java programming language and also CorelDraw X5 , and Adobe Photoshop tools. The design and manufacture of this game is aimed to attract children aged equivalent of sixth grade elementary school students in learning mathematics .Â Keyword : math game, VI grade of Elementary School, android.